Interpreting detrital modes and geochemistry of sandstones from the late Paleozoic Tepuel-Genoa Basin: Paleogeographic implications (Patagonia, Argentina). (December 2020) - Ciccioli, Patricia L.; Limarino, Carlos O.; Isbell, John L.; Taboada, Arturo C.; Pagani, María A.; Gulbranson, Erik L.
Abstract: The provenance of sandstones deposited in the late Paleozoic Tepuel-Genoa Basin is analyzed in this paper. Five sections were sampled in Esquel, Sierra de Tepuel, Sierra de Tecka, El Molle, and Río Genoa areas for petrographic and geochemical studies. The sandstones in the Tepuel-Genoa Basin are dominated by feldspathic litharenites and litharenites, showing lithic fragments of volcanic and sedimentary rocks in the Valle Chico Formation and medium-to high-grade metamorphic rock clasts in the rest of the units. Detrital modes of seventy-five sandstones samples from the Valle Chico, Pampa de Tepuel, Mojón de Hierro, and Río Genoa formations were counted and analyzed. Seven modal components have discriminant value for identifying provenance areas (Qm, Qi, Lv, Lmm-h, Lm-Lp, Lm, Qpm). These modal components allow identification of three petrofacies: 1. Quartzose-lithic (Qm69 Lv2 Lm29 ), 2. Quartzose (Qm89 Lv4 Lm7 ) and 3. Volcanic-sedimentary (Qm60 Lv38 Lm1 ). The quartzose-lithic petrofacies is mainly composed of monocrystalline quartz, medium- and high-grade metamorphic clasts and polycrystalline quartz with cataclastic texture, this assemblage is interpreted as being derived from the crystalline rocks that form the Deseado Massif. The quartzose petrofacies is composed of monocrystalline quartz with scarce contributions of metamorphic clasts and traces of volcanic fragments; the provenance area is ascribed to sedimentary terrains, which most likely covered part of the Deseado Massif. The volcanic-sedimentary petrofacies is comprised of volcanic (acidic and intermediate rocks) and sedimentary (sandstone and mudstone) clasts, with discrete amounts of quartz grains with idiomorph shapes and embayments. This assemblage may correspond to material supply from the Devonian-Early Carboniferous accretionary complex developed in Chile or the unroofing of the western volcanic arc located in the central part of Patagonia. The validity of the three defined petrofacies was evaluated using Principal Component Analysis and triangular compositional diagrams; both methods show good separation and lack of overlap between the three petrofacies. Major (Si, Al, Fe, Na, K) and trace-REE elements (Zr, Th, Sc, Hf) were used to improve the petrographic information. The relation SiO2 against K2 O/Na2 O indicates that the Pampa de Tepuel and the Mojón de Hierro formations correspond to a passive margin, while the Valle Chico and Río Genoa formations represent different types of active continental margins. The Th/Sc and Zr/Sc ratios and the Th-Hf-Co distributions indicate that the sandstones of the Tepuel Group were formed from rocks compatibles with the average composition of the upper continental crust. Highlights: Detrital modes of the late Paleozoic Tepuel-Genoa Basin in Patagonia (Argentina) are analyzed. Geochemical data of sandstones of this basin are presented. Three petrofacies (Quarztoze, Quarztose-lithic, and Volcanic-sedimentary) are defined. The basement of the Macizo del Deseado and Chilean accretionary complexes are proposed as the main source areas.